WAHHABISM AND JADIDISM N ISLAMIC CONSCIOUSNESS N DAGHESTAN: PARALLELS AND CONTRADICTIONS - ABDULAGATOV, Zaid (CENTRAL ASIA AND THE CAUCASUS, 2006)
Effective opposition of religious extremism requires mastering the entire range of conceptual systems appropriate for the situation at hand. And not many of those who write about Islam and its problems miss the opportunity to mention fundamentalism, Salafism, Wahhabism, Jadidism, and other similar concepts. On the one hand, this attention to academics should be hailed since, otherwise, it would be difficult to conceptualize our knowledge; while on the other, the multitude of different approaches breeds a multitude of different ideas, whereas science should strive for the opposite. A lack of harmony when it comes to concepts and terms undermines our concerted efforts aimed at fighting and defeating religious extremism. There is no agreement—in the academic and religious communities alike—on the interpretations of Jadidism and Wahhabism. This fully applies to the Republic of Daghestan. There is the opinion that the concept of “fundamentalism” cannot be applied to Wahhabism and its description, Daghestan being no exception in this case.1 Both in Russia and the West the term “fundamentalism” is obviously abused.2 This is very true: the term fails to describe the very essence of Wahhabism: it is too limited to describe Wahhabi specifics. It is indispensable, however, and serves a useful purpose when it comes to identifying its special and particular features. From this point of view, the concept of fundamentalism is indispensable for any discussion of the nature of Wahhabism. It should not be abused, however. V. Naumkin has pointed out that certain authors tend to apply the term to an extremely wide spectrum of religious phenomena: “renovation,”3 “revisionism,”4 “mod ernism,”5 “revivalism,” and “traditionalism.” Without going into details, it would be wise to base an analysis of fundamentalist trends in Islamic confessions on the concept of Salafism. It has already been accepted by the academic community as an anchor term used to describe the basic, and shared, content of all Islamic fundamentalist trends. Islam, one of the best encyclopedic dictionaries, derives the term “Salafi” from “Salaf,” meaning “ancestors” or “precursors.” Salafi is a blanket term applied to all Muslim religious figures who during their lifetime called on the faithful to imitate the lifestyle and religious convictions of the early Muslim community and the “righteous ancestors” (al-salaf al-salihun). They described all later developments as “bid’ah” (heresy).6 Salafism, and fundamentalism of all other hues for that matter, means excessive loyalty to the original confessional ideas that force its followers to reject all later changes and reforms touching upon fundamentals and values.